Urological Cancer 2022 - López, José I.; Manini, Claudia (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the urological sphere, the number of tumor malignancies caused by cancer is continuously growing in Western countries. Although this is mainly due to the contemporary increase in the life expectancy of people in these geographic areas, many other factors are also contributing to this growth. Urological cancer is a complex and varied disease which affects different organs and mainly affects the male population. In fact, in most statistics, kidney, prostate, and bladder cancer are regularly included in the top-ten list of the most frequent neoplasms in males. The female population, however, has also been increasingly affected by renal and bladder cancer in the last decade. From these facts, it is clear that urological cancer is a problem of major concern in developed societies. This Topic Issue of Cancers intends to shed some light on the complexity of this field and will consider all useful and appropriate contributions from scientists and clinicians in order to improve urological cancer knowledge for patients' benefit.